Correction: Investigating the association between diabetes and carpal tunnel syndrome: A systematic review and meta-analysis approach. - Elaheh Sanjari; Hadi Raeisi Shahraki; Lusine G Khachatryan; Abdollah Mohammadian-Hafshejani (PLoS ONE, 2025)
[This corrects the article DOI: 10.1371/journal.pone.0299442.].